Video sebagai Media Pembelajaran Bahasa Jepang: Studi Respon Mahasiswa terhadap Tema Pariwisata Lokal : Video as a Medium for Japanese Language Learning: A Study of Students’ Responses to the Theme of Local Tourism - Sri Wahyu Widiati; Zuli Laili Isnaini; Intan Suri; Mutiara Rahmi Utami; Putri Rahayuningtyas; Merri Silvia Basri (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
The purpose of this research is to explore students' perceptions of the use of Japanese language learning videos that highlight local tourism themes in Riau Province. The methodology employed is a quantitative approach with a survey design involving 30 students from the Japanese Language Education Program at Universitas Riau. Data collection was conducted using a questionnaire consisting of closed-ended questions measured by a Likert scale to assess important criteria related to the use of teaching media. The results indicate a positive response regarding the learning videos with an average score of 90%. Meanwhile, 100% of respondents stated that this educational product is capable of providing insights into Riau tourism. The representation aspect of local Riau culture was rated at 97%, while daily applicable content reached 78.8%. The motivation to learn increased to 93.9%, as reported by students who felt encouraged to learn further. The findings emphasize the importance of integrating local cultural themes into foreign language learning, especially Japanese, and demonstrate that learning videos can be an effective solution to meet educational needs in the tourism sector. Recommendations for further development of teaching products are provided to enhance the effectiveness of Japanese language education in Indonesia.